Analysis of the Main Character's Moral Values in the Novel Suti by Sapardi Djoko Damono - Dasy, Saraswaty Sinun; Lering, Maria Ermelinda Dua; Owon, Robertus Adi Sarjono (Jurnal Riset Ilmu Pendidikan, 2023)
The problem in this research is to find the moral value of the main character in the novel Suti by Sapardi Djoko Damono. This research is a literary work through document analysis in the form of literature review, which is qualitative in nature. Based on the results of the research and discussion in the novel Suti by Sapardi Djoko Damono, the focus is on the analysis and inference of the moral values of the main character Sutini. This study uses a literary structural approach with the main character being the object of research. The depiction of the pattern of human behavior by itself depicts Suti as a human being who is open and not easily discouraged. The pattern of human behavior with other humans shows that Suti is a friendly and sociable person. The pattern of human behavior with God shows that Suti is a person who always longs to meet God. Thus, the main character Suti has moral values of being open, courageous, not easily discouraged, friendly and longing